Vpliv agronomskih parametrov na gostoto in dolžino listnih rež pri ameriškem slamniku (Echinacea purpurea (L.) Moench) - Kolar, Darja (Folia biologica et geologica, 2018)
Herbal preparations from Echinacea purpurea (purple coneflower) are often used in common cold and flu because of their immune stimulatory effects. The popularity of these products has grown considerably in recent years, and there is increasing market supply. Numerous studies have been made investigating the cultivation, quantification of active ingredients, safety and efficacy of Echinacea purpurea. In this study we determined the density of the leaf stomata on the lower and upper sides of the leaves and the length of the leaf stomata on the lower side of leafs in 213 samples of E. purpurea plants, which differed in the cultivation parameters. Density and length were measured with the microscopic examination of the imprint of the epidermis, which we made with clear nail varnish. We checked the effect of the size of the leaf and the influence of the measuring position on the leaf. We found that the densities and the length of the stomata were significantly different across the width of the leaf. Therefore, we carried out measurements at a constant position in the middle between the central vein and the leaf edge. The most pronounced parameter influencing the stomata properties was season of harvesting. In the autumn harvest compared to summer, the density of the stomata of the upper side was 66% higher (p <0.001) and the stomata length on the lower side was 11% higher (p <0.001). We did not find significant effects of any of the studied agronomical parameters (irrigation, age of plants and location of plantation) on the properties of leaf stomata. We also observed a significant negative correlation between the stomata density and stomata length and a positive correlation between the stomata density of the lower on the upper side of the leaf. We observed that larger plants had longer stomata and lower stomata density compared to smaller plants. This effect was statistically significant but small. Plants with a higher percentage of dry mass in harvested biomass (lower water content) had a higher stomata density and smaller stomata lengths, but the correlation was significant only in summer harvest. There are no significant correlations between chicoric and caftaric acids concentrations and the stomata density or length.
Keywords: Ameriški slamnik; Echinacea purpurea; gostota rež; leaf stomata; listne reže; purple coneflower